Keterampilan Bertanya Siswa Kelas V pada Pembelajaran Tematik Materi IPA - Hardianty, Okta Dwi; Erviana, Lina; Burhanuddin, Afid (PGSD STKIP PGRI Pacitan, 2024)
This study aims to describe 1) the learning process of fifth grade students in the thematic learning of natural science material at SD Negeri 2 Jetak, 2) the questioning skills of fifth grade students in thematic learning of natural science material at SD Negeri 2 Jetak. This type of research is qualitative research using descriptive methods. The subjects of this study were fifth grade students at SD Negeri 2 Jetak. Data collection techniques, by way of observation, interviews, and documentation. Data analysis techniques use the Miles and Huberman models, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that: 1) The learning process of fifth grade students during the thematic learning of science material has been carried out well, there has been good interaction between teachers and students. Thematic learning in class V uses two textbooks, namely thematic package books and thematic LKS books. 2) The questioning skills of fifth grade students in thematic learning vary greatly, some students feel happy when asking questions during class learning, because they can get rewards in the form of additional scores. As well as the skill of asking questions the teacher also participates in provoking and motivating students to ask questions, so that there is an increase in student activity in asking questions. So students who have good questioning skills tend to be more active during the learning process and have achievement, compared to students who don't have questioning skills.